Efektivitas Internal Walking Training (IWT) terhadap Penurunan Tekanan Darah pada Peserta Program Pengelolaan Penyakit Kronis (Prolanis) di Puskesmas Imogiri 2 - Novia Jati Ramadhani; Andi Musdalifah; Kurnia Duwi Anggi Meilasari; Veni Fatmawati; Novika Kurniawati (Jurnal Riset Daerah, 2026)
Aging often leads to a decline in physiological function among the elderly, with hypertension being the primary noncommunicable disease that further exacerbates the risk of cardiovascular problems. In Indonesia, the prevalence of hypertension reaches 34.1% (Riskesdas 2018), with the highest rate among the elderly in Bantul, which recorded 83,932 cases in 2020. This study was designed to assess the effectiveness of Internal Walking Training (IWT) in reducing systolic and diastolic blood pressure among older adults with hypertension in Sriharjo Village, Bantul. The study employed a quasi-experimental design with a one-group pre-test post-test design, involving 43 older adult participants selected through purposive sampling. The IWT intervention was conducted once for 30 minutes, consisting of 5 cycles (3 minutes of slow walking followed by 3 minutes of brisk walking), with blood pressure measurements taken using a digital sphygmomanometer before and after the intervention; data analysis was performed using the Wilcoxon Signed Rank Test. The results showed a significant decrease in both systolic and diastolic blood pressure following the IWT intervention. Thus, IWT has been proven effective as a simple non-pharmacological intervention for controlling hypertension in the elderly.